General education: curricular and pedagogical issues - Robiah Sidin,; Nor Azizah Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper provides an overview of general education from the curriculum and the pedagogical perspectives. it describes the philosophy of the National University of Malaysia (UKM), and the place of general education in the context of UKM’s philosophy. It also describes the state of practice of general education at UKM as perceived by students and lecturers involved in learning and teaching some courses in general studies. The paper then highlights some curricular and pedagogical issues, including the concept and objectives of general education, lecturers preparation, suitability of courses offered, students’ participation, teaching methods and assessments. Although this paper raises more questions than answers, an attempt is made to suggest how some of the issues could be resolved.